2019
DOI: 10.1186/s12014-019-9227-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the plasma proteome of nonhuman primates during Ebola virus disease or melioidosis: a host response comparison

Abstract: BackgroundIn-depth examination of the plasma proteomic response to infection with a wide variety of pathogens can assist in the development of new diagnostic paradigms, while providing insight into the interdependent pathogenic processes which encompass a host’s immunological and physiological responses. Ebola virus (EBOV) causes a highly lethal infection termed Ebola virus disease (EVD) in primates and humans. The Gram negative non-spore forming bacillus Burkholderia pseudomallei (Bp) causes melioidosis in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
1
11
2
Order By: Relevance
“…In our study, iPSC-derived hepatocytes downregulate the coagulation cascade 2-7 dpi. We also do not observe an increase in acute phase reactants that has been observed in NHPs (69). iPSC-derived hepatocytes downregulate the expression of critical clotting factors and plasma proteins, including ALB, brinogen chains alpha, beta, and gamma (FGA, FGB, and FGG), protein c (PROC), and F3 as early as 2 dpi.…”
Section: Discussioncontrasting
confidence: 46%
“…In our study, iPSC-derived hepatocytes downregulate the coagulation cascade 2-7 dpi. We also do not observe an increase in acute phase reactants that has been observed in NHPs (69). iPSC-derived hepatocytes downregulate the expression of critical clotting factors and plasma proteins, including ALB, brinogen chains alpha, beta, and gamma (FGA, FGB, and FGG), protein c (PROC), and F3 as early as 2 dpi.…”
Section: Discussioncontrasting
confidence: 46%
“…The CP of eligible donors in areas where an epidemic disease has broken out can offer specific, artificially obtained, passive immunity against the local infectious agent [18] . Plasma protein levels can readily be affected by bacterial and viral infections [19] . Identifying specific viral protein biomarkers is a possible strategy to identify sources and types of infection [20] .…”
Section: Challenges Of Biological Requirementsmentioning
confidence: 99%
“…Plasma protein levels can readily be affected by bacterial and viral infections [19] . However, specific viral protein biomarkers can be used to identify the source and type of infections [20] .…”
Section: Testing Phasementioning
confidence: 99%
“…Amongst the top upregulated genes were C4BPB (logFC = 3.33) and C4BPA (logFC = 2.20), which are proteins responsible for regulating the complement cascade upon tissue damage and modulating the coagulation cascade through its interaction with protein S 24,34 . Previous studies have shown the importance of inhibition of C4BP in the context of pathogenic infections including IAV and ebola virus 27,37 . Our next step was to determine if the protein expression levels tracked the genetic expression levels of C4BP upregulation upon loss of sigma-2R/TMEM97.…”
Section: Disucssionmentioning
confidence: 99%